Pemanfaatan Matrik Tindak Lanjut Hasil Pemeriksaan Untuk Meningkatkan Efektivitas Pengawasan di Inspektorat Daerah Kabupaten Sidenreng Rappang - Herlinda; Damis, Sariana (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
A Local governments have an important role in carrying out oversight functions to ensure accountability and transparency. One important oversight agency is the Regional Inspectorate, which is tasked with conducting audits of local government performance and finances. Follow-up of Audit Results (TLHP) is a key element in ensuring that audit findings are corrected and implemented effectively. However, in its implementation, there are often obstacles, such as lack of coordination and constraints in monitoring. Therefore, a follow-up of audit results (TLHP) matrix is proposed as a solution to organize and monitor this follow-up process. The TLHP matrix helps to map findings, set priorities, and clarify the division of tasks and deadlines for completion. This research was conducted through an internship program at the Regional Inspectorate of Sidenreng Rappang Regency to examine the application of the TLHP matrix in improving the effectiveness and efficiency of follow-up. The results showed that the use of the TLHP matrix proved effective in improving coordination, reducing obstacles, and accelerating the follow-up process. The use of information technology also plays an important role in supporting the effectiveness of this matrix. It is recommended that the next internship program can increase training on procedures and the use of the matrix as well as provide briefings on more sophisticated technology to support student adaptation in the field